Faktor-Faktor yang Mempengaruhi Turnover Intention Karyawan CV. Dua Putri Mojo - Lu'luatuwwafiroh Lu'luatuwwafiroh; Mia Utami; Jailani Jailani; Bintoro Ariyanto (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: This stufy aims to examine and compare how salary satisfaction, work environment and leadership affect the turnover intentions of employees at CV. Dua Putri Mojo, as well as to identify wich of these variables exerts the most significant influence. Methodology: This research employs a quantitative approach, utilizing surveys to gather primary data via questionnaires. This research employs various method of multiple regression analysis. The researcher created the data collection instrument utilizing the SPSS statistics software. Results: Research demonstrates that satisfaction with salary, work environment and leadership significantly negatively impact the turnover intention od CV. Dua Putri Mojo. While all three factors are noteworthy, the findings indicate that the work environment exerts the greatest influence in mitigating turnover intention. The t-test table provides comprehensive information about the analytical outcomes. Conclusions: Salary satisfaction, work environment, and leadership have a significant negative effect on employee turnover intention at CV. Dua Putri Mojo. These factors are essential for retaining employees and reducing company costs. Limitations: This research conducted among the employees of CV. Dua Putri Mojo, wich means applying the findings to other organizations particularly those outside the industry and with varying business sizes should be approached with caution. Other elements that may influence turnover intention, such as career opportunities, organizational commitment, and individual characteristics, were not examined in this study. Contribution: Practical Implications: CV. Dua Putri Mojo can organize transformational leadership training for its managers. Theoretical Implications: this research reinforces the concept of transformational leadership regarding the intention to leave in small organizations.